Тактично-орієнтовані підходи податкового планування в умовах сталого розвитку ринку - Чернікова, І. Б.; Кирильєва, Л. О.; Нестеренко, І. В.; Кузнецова, Світлана Олександрівна (Харківський державний університет харчування та торгівлі, 2020)
Розкрито сутність тактично – орієнтованих підходів податкової гармонізації за умов сталого розвитку ринку. Встановлено теорети-кометодологічну та практичну потреби у використанні податкового планування як концептуального елемента формування механізму оподаткування у проактивній стратегії розвитку. Доведено, - мінімізація податкових ризиків стає якісним критерієм оцінювання управлінських рішень в сегменті податкових відносин між державою і ринковими структурами.

The essence of tactically-oriented approaches of tax harmonization under the conditions of sustainable market development is shown by the authors. The article examines the criterion differences of tax planning methods (current financial control, preliminary tax examination, comparative analysis) from illegal tax evasion in a proactive sustainable development strategy in the segment of tax relations between the state and market structures. The article highlights the problem issues that arise in the process of tax planning: it substantiates its principles and methods concerning the stages of harmonization of tax relations; it gives the theoretical analysis of current trends in tax planning which determine the formation of methodology in this area. Based on the results of the study, the theoretical, methodological and practical needs for using tax planning as a conceptual element in the formation of the taxation mechanism taking into account the identified stable relationships, harmonization of relations between economic agents have been established, since it is proved that at the present stage of the development of market economy, the criterion for assessing the quality of management decisions in taxation should rather be the minimization of tax risks instead of profit maximization in order to improve the financial state and market value. During risks assessment attention is paid to the use of information from third parties – banks, exchanges, state institutions (agencies which fight against money laundering, departments of land and property rights registration) in the chosen proactive strategy of the effective mechanism building for regulatory authorities with taxpayers coordinated interaction in the taxation sphere.
Tactically-oriented approaches of tax planning under the conditions of sustainable market development
Keywords: управління ризиками; проактивна стратегія; платники податків; економіка; tax planning; tax payers; risk management; proactive strategy; sustainable development